2013
DOI: 10.4161/spmg.25465
|View full text |Cite
|
Sign up to set email alerts
|

NC1 domain of collagen α3(IV) derived from the basement membrane regulates Sertoli cell blood-testis barrier dynamics

Abstract: The blood-testis barrier (BTB) is an important ultrastructure for spermatogenesis. Delay in BTB formation in neonatal rats or its irreversible damage in adult rats leads to meiotic arrest and failure of spermatogonial differentiation beyond type A. While hormones, such as testosterone and FSH, are crucial to BTB function, little is known if there is a local regulatory mechanism in the seminiferous epithelium that modulates BTB function. Herein, we report that collagen α3(IV) chain, a component of the basement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 77 publications
3
37
0
1
Order By: Relevance
“…Rat collagen α3(IV) chain NC1 domain was cloned as previously described (34), which also served as the template to clone pCI‐neo/NC1 that contained the putative signal peptide (SP) of rat collagen α3(IV) chain, namely pCI‐neo/rat SP (rSP)‐NC1. Four sequential overlapping PCRs were performed to add the putative SP (Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Rat collagen α3(IV) chain NC1 domain was cloned as previously described (34), which also served as the template to clone pCI‐neo/NC1 that contained the putative signal peptide (SP) of rat collagen α3(IV) chain, namely pCI‐neo/rat SP (rSP)‐NC1. Four sequential overlapping PCRs were performed to add the putative SP (Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, what molecule(s) and/or signaling pathway(s) are involved in coordinating both the events of spermiation and BTB restructuring which take place simultaneously at stage VIII but across the seminiferous epithelium? It is likely that biologically active fragments of laminin chains that are formed during apical ES degeneration at late stage VIII are involved in coordinating these events [51, 52], however, the biology of collagen fragments (e.g., non-collagenous domain 1, NC1) generated at the basement membrane that modulates BTB dynamics [110, 111] remains to be better elucidated. Also, does cytokine(s) (e.g., TGF-β3, TNFα) play any roles in these events since studies have shown that cytokines released by Sertoli and/or germ cells into the microenvironment of the ES regulate cell adhesion [112-114]?…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…On the other hand, recent studies have shown that BTB dynamics in the rat testis are supported and regulated by local functional axis involving biologically active fragments released from the apical ES (at the Sertoli-spermatid interface in the adluminal compartment from step 8–19 spermatids) such as the F5 peptide from the laminin chains [3032], and also peptides from the collagen α3 (IV) chain (e.g., non-collagenous 1, NC1, domain peptide) [33] and laminin α2 chain (e.g., 80 kDa fragment) [34, 35]. These findings are also supported by studies using toxicant-induced Sertoli cell injury animal models, such as the use of phthalates [36, 37].…”
Section: Introductionmentioning
confidence: 99%